Therapeutic Drug Monitoring of Ceftazidime-Avibactam Concentrations in Carbapenem-Resistant K. pneumoniae-Infected Patients With Different Kidney Statuses - Teng, Xin-Qi; Qu, Qiang; Luo, Yue; Long, Wen-Ming; Zhuang, Hai-Hui; Xu, Jiao-Hua; Wen, Yu-Xin; Zhang, Hui-Lin; Qu, Jian (Frontiers in Pharmacology, 2022)
Aims: Carbapenem-resistant K. pneumoniae (CRKP) is the most common carbapenem-resistant Enterobacteriaceae with high mortality. Ceftazidime/avibactam (CAZ-AVI) has exhibited excellent in vitro activity in vivo against CRKP. However, the efficacy of CAZ-AVI in KPC-producing CRKP-infected patients with different kidney statuses varies, such as renal insufficiency, normal renal function, and augmented renal clearance (ARC). We explored the use of therapeutic drug monitoring (TDM) to evaluate the concentration and efficacy of CAZ-AVI in CRKP-infected patients with different kidney statuses. Methods: Serum concentrations for CAZ and AVI were determined by the High-Performance Liquid Chromatography method. Bacterial identification, routine susceptibility testing, renal function index, and others were performed in standard protocols in the hospital’s clinical laboratories. Results: In the two patients with ARC, case 1 used CAZ-AVI 2.5g q6h with good efficacy, and the concentrations were up to the pharmacokinetics/pharmacodynamics targets. Case 2 used 2.5g q8h with invalid effectiveness, and AVI Cmin was only 0.797 mg/L, which is lower than the PK/PD target. Case 3 was renal insufficiency using CAZ-AVI 1.25 q8h, and case 4 was normal renal function using 2.5g q8h. Their concentrations were both up to the PK/PD targets. Conclusion: TDM results demonstrated that CAZ-AVI steady-state plasma concentration varies among patients with different kidney statuses, providing evidence for the utility of TDM of CAZ-AVI in individualized drug dose adjustment. ARC patients may need more CAZ-AVI daily doses than the standard dose.